Manufacturing growth and agglomeration effects - Fafchamps, M (University of Oxford, 2004)
This paper investigates the effect of location-specific competition and diversity on manufacturing growth. We find strong and robust evidence of agglomeration effects: competition is good for growth but diversity is not. However, none that the effects are due to productivity or wages. First, agglomeration variables have on growth the opposite effect than on individual firm productivity. Second, controlling for productivity directly does not reduce the significance or magnitude of agglomeration variables. Agglomeration variables measure something that is relevant for growth, but it is not productivity. We also find that a rise in productivity raises subsequent employment and investment, but has no effect on firm entry and exit.